Palm-Sorbent: Acid-Impregnated Palm Fibre for Sorption of Cr (VI) from Chrome Plating Effluent - Naimah, Ibrahim (Malaysian Invention and Design Society (MINDS), 2010)
Naimah Ibrahim and her team won silver for Palm-Sorbent: Acid-Impregnated Palm Fibre for Sorption of Cr (VI) from Chrome Plating Effluent. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.